Zhodnocení ekonomické prosperity Královéhradeckého kraje - Hubená, Veronika (Univerzita Pardubice, 2006)
Tato diplomová práce se zabývá nejprve obecně regionální politikou, regionální politikou Evropské Unie a České republiky. Další pozornost je věnována regionální politice Královéhradeckého kraje a jeho ekonomickému zhodnocení. Ve své práci jsem se zaměřila zejména na základní makroekonomické ukazatele (především hrubý domácí produkt), dále na oblast odvětvové a organizační struktury a trhu práce. Královéhradecký kraj je porovnáván jak v rámci jednotlivých okresů kraje (Hradec Králové, Jičín, Náchod, Rychnov nad Kněžnou, Trutnov), tak v rámci jednotlivých krajů České republiky.

This thesis is generally engaged in regional policy. A part presented the regional policy of European Union and Czech Republic. Further attention is dedicated to regional policy of Hradec Kralove region and its economic estimation. In my thesis I paid attention to the basic macroeconomics indices (particularly the gross domestic product), then to the sphere of branch and organizational structure and of employment market. Hradec Kralove region is compared to the single districts of region (Hradec Kralove, Jicin, Nachod, Rychnov nad Kneznou, Trutnov) and also to the single region of Czech Republic.
Estimation of economic prosperity of Hradec Kralove region
Keywords: Hradec Kralove region; estimation of economic prosperity; Regional Policy; European Union; Královéhradecké kraj; ekonomické zhodnocení; prosperita; Regionální politika; Evropské unie